EUFEMISME DALAM UNGKAPAN TRADISIONAL DAERAH MELAYU DI JAMBI - Rustam Rustam (Pena : Jurnal Pendidikan Bahasa dan Sastra, 2015)
The traditional Javanese Malay expression of Jambi folklore is part of a culturally distributed and traditionally passed down tradition among different groups of people with different verifications, whether in the form of a word utterance accompanied by deeds or by behavior or acts only, for example, adat, proverb, petitih-petitih, folklore. This research aims to describe the form of euphemism in traditional Jambi Malay expression and to describe the meaning of euphemism in Jambi Malay traditional expression. The method used in this research is qualitative descriptive method. The result of the research explains that euphemism in Jambi Malay traditional expression is based on semantic approach in terms of linguistic form of words, phrases, and clauses. The meaning of euphemism in traditional Jambi Malay expression is used in certain time, place and certain scope, for example in the context of adat, religion, government, relations among peoples and have noble values ​​about Jambi Malay cultural civilizationsuch as honesty, courage, imitation, health, kinship, sincerity.